The Evaluation of the Utilization of the 2018 Village Funds in Bintan District and Lingga District - Adhayanto, Oksep; Arianto, Bismar; Winatawira, Winatawira; Suryadi, Suryadi; Nurhasanah, Nurhasanah (Jurnal Bina Praja, 2019)
The Village funds are part of the State Revenue and Expenditure Budget which are allocated for villages and disbursed through the district/city expenditure budget. During the period of 2015 – 2018, two village heads (village of Malang Rapat and Penaga) were the suspects of corruption cases in Bintan District in the province of Riau Islands. There was no evaluation of the use of the village funds by the district government. The objective of this study was to gain an insight into the use of village funds in the province of Riau Islands. The study problem was how to evaluate the use, impact, and constraints in the utilization of village funds in the province of Riau Islands in 2018 (Case study in Bintan District and Lingga District). This study used a qualitative descriptive method, using interviews and observations for data collection. The results showed that a large portion of village funds was used for physical development in the village, while human development in the village was not yet properly implemented due to the limited allocation of village funds for empowerment and community development. The impact of village funds felt by the community for the addition of physical facilities in the village was significant, while the impact on empowerment and economy of the community was not. The constraints of the usage of the village funds were regulation, human resources, and coordination.